2019
DOI: 10.1016/j.cell.2019.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Dynamics Regulating Brain and Behavioral State Transitions

Abstract: Prolonged behavioral challenges can cause animals to switch from active to passive coping strategies to manage effort-expenditure during stress; such normally adaptive behavioral state transitions can become maladaptive in psychiatric disorders such as depression. The underlying neuronal dynamics and brainwide interactions important for passive coping have remained unclear. Here, we develop a paradigm to study these behavioral state transitions at cellular-resolution across the entire vertebrate brain. Using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
238
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(276 citation statements)
references
References 95 publications
13
238
1
1
Order By: Relevance
“…In this study we investigated the functional development of habenular circuits across multiple developmental stages of zebrafish from relatively simpler larvae to juvenile zebrafish with complex behaviours (Amo et al, 2014;Andalman et al, 2019;Chou et al, 2016;Dreosti et al, 2015;Hinz and de Polavieja, 2017;Ksenia Yashina, 2019;Valente et al, 2012). The use of juvenile zebrafish is getting increasingly popular due to their transparent brains and expanded behavioural repertoire that requires habenular function (Andalman et al, 2019;Dreosti et al, 2015;Hinz and de Polavieja, 2017;Valente et al, 2012;Yashina et al, 2019). Our results revealed that as the zebrafish develop from larval to juvenile stage, habenular circuits undergo multiple transitions in its architecture, sensory computations and intrinsically generated spontaneous activity, which could support the expansion of the behavioural repertoire in developing zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study we investigated the functional development of habenular circuits across multiple developmental stages of zebrafish from relatively simpler larvae to juvenile zebrafish with complex behaviours (Amo et al, 2014;Andalman et al, 2019;Chou et al, 2016;Dreosti et al, 2015;Hinz and de Polavieja, 2017;Ksenia Yashina, 2019;Valente et al, 2012). The use of juvenile zebrafish is getting increasingly popular due to their transparent brains and expanded behavioural repertoire that requires habenular function (Andalman et al, 2019;Dreosti et al, 2015;Hinz and de Polavieja, 2017;Valente et al, 2012;Yashina et al, 2019). Our results revealed that as the zebrafish develop from larval to juvenile stage, habenular circuits undergo multiple transitions in its architecture, sensory computations and intrinsically generated spontaneous activity, which could support the expansion of the behavioural repertoire in developing zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…To study the functional development of zebrafish habenula, we focused on three developmental stages: 3dpf (early larval stage), 6dpf (late larval stage) and 21dpf (juvenile stage). During these periods, zebrafish transition from self-feeding larvae (via the yolk sac) to an external feeding juvenile animal with more complex behaviours including those involving habenular circuits (Agetsuma et al, 2010;Amo et al, 2014;Andalman et al, 2019;Dreosti et al, 2015;Hinz and de Polavieja, 2017;Valente et al, 2012). First, we visualized the gross morphology of Hb in Tg(elavl3:GCaMP6s) (Vladimirov et al, 2014) zebrafish, labelling most habenular neurons.…”
Section: New Neurons and New Inhibitory Connections Are Added To Habementioning
confidence: 99%
See 3 more Smart Citations